D-ribose-L-cysteine modulates paradoxical sleep deprivation-induced neurological impairments: anxiolytic and antioxidative study in rat model. Issue 1 (31st December 2022) - Abayomi, Taiwo; Tokunbo, Olorunfemi; Oroyemi, Oluwatobiloba; Abayomi, Olawale; Osuntokun, Opeyemi; Falana, Benedict; Adeniyi, Temidayo
ABSTRACT: This study evaluated the anxiolytic and antioxidative potential of DRLC on behavioral deficits, and neuronal perturbations in the hippocampus following paradoxical sleep deprivation in adult Wistar rats. Animals were paradoxically sleep deprived for 7 days ; DRLC (75 mg/kg b.w of Riboceine TM ) was pre- and post-administered for 21 days before and after paradoxical sleep deprivation. Thereafter, behavioral study was conducted to assess fear and anxiety, animals were sacrificed and biochemical analysis of oxidative stress markers and histomorphology of the hippocampus was performed. Behavioral assessments revealed that PSD elicited increased anxiety levels as demonstrated by reduced line crossing, reduced habituation time, and increased freezing time in OFT as well as increased time spent in closed arms of EPM. Also, oxidative stress levels were elevated by PSD with significantly decreased activities of catalase (CAT), superoxide dismutase (SOD) and glutathione (GSH) concentration as well as increased Malondialdehyde concentrations in the blood serum. However, pre-and post-treatment with DRLC significantly prevented and reduced anxiety levels and oxidative stress levels as well as prevented and repaired neuronal hippocampal damage associated with PSD respectively. In conclusion, DRLC was able to modulate oxidative stress-driven alterations and perturbed emotionality linked with PSDthrough its anxiolytic and antioxidative properties. Abbreviations : D-ribose-L-cysteine(DRLC); Catalase(CAT); Glutathione transferase(GSH); Superoxide dismutase(SOD); Non-rapid eye movement(NREM); Rapid eye movement(REM); Paradoxical sleep deprivation(PSD); Elevated plus maze(EPM); Open Field test(OFT)